2022
DOI: 10.1101/2022.12.07.519508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mild SARS-CoV-2 infection results in long-lasting microbiota instability

Abstract: Viruses targeting mammalian cells can indirectly alter the gut microbiota, potentially compounding their phenotypic effects. Multiple studies have observed a disrupted gut microbiota in severe cases of SARS-CoV-2 infection that require hospitalization. Yet, despite demographic shifts in disease severity resulting in a large and continuing burden of non-hospitalized infections, we still know very little about the impact of mild SARS-CoV-2 infection on the gut microbiota in the outpatient setting. To address thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
5
1
1
Order By: Relevance
“…In this study, we investigated how SARS-CoV-2 impacts the gut microbiome of women (both WLHIV and HIV-negative) and their infants. We found that SARS-CoV-2 altered the microbiome; however, the changes we observed were less pronounced than described in several previous studies that found SARS-CoV-2 alters the gut microbiome signi cantly after infection 5,7,13,14,16,17,19,20,[50][51][52][53][54] . This result could be due, in part, to the clinically mild SARS-CoV-2 cases in our study 23 .…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In this study, we investigated how SARS-CoV-2 impacts the gut microbiome of women (both WLHIV and HIV-negative) and their infants. We found that SARS-CoV-2 altered the microbiome; however, the changes we observed were less pronounced than described in several previous studies that found SARS-CoV-2 alters the gut microbiome signi cantly after infection 5,7,13,14,16,17,19,20,[50][51][52][53][54] . This result could be due, in part, to the clinically mild SARS-CoV-2 cases in our study 23 .…”
Section: Discussioncontrasting
confidence: 80%
“…In addition, children who are HIV-exposed but uninfected (HEU) have been reportedto have an altered gut microbiome compared to HIV-unexposed and uninfected (HUU) children 11,12 . SARS-CoV-2 infection has also been observed to alter the gut microbiome for both adults and infants and can cause long lasting microbiota disruption 7,[13][14][15][16] . Some studies have found speci c gut species to be associated with severity of SARS-CoV-2 symptoms, ranging from mild/asymptomatic to severe.…”
mentioning
confidence: 99%
“…Intestinal barrier impairment, dysbiosis of gut microbiota, and perturbation of metabolites are prevalent occurrences among individuals with COVID‐19. Extensive research has consistently shown the association between microbiota composition and the morbidity, exacerbation, and mortality rates seen in COVID‐19 patients 51–55 . The gut microbiota facilitates the assessment of sickness severity in individuals with COVID‐19 56 .…”
Section: Discussionmentioning
confidence: 99%
“…patients. [51][52][53][54][55] The gut microbiota facilitates the assessment of sickness severity in individuals with COVID-19. 56 From a mechanical standpoint, it is observed that COVID-19 disrupts the composition of gut microbiota and metabolites.…”
Section: Potential Confounding Factors and Mechanismsmentioning
confidence: 99%
“…An in-depth assessment demonstrated an evident correlation between viral infection signatures and the enrichment of gut pathogens, including Collinsella aerofaciens, Collinsella tanakaei, Streptococcus infantis , and Morganella morganii , even in the absence of gastrointestinal manifestations ( 47 ). Although the Omicron variant is known to cause relatively mild symptoms with marginal invasiveness in humans and gut models, all SARS-CoV-2 variants of concerns remarkably disrupted the mouse gut microbiota ( 103 ). Surprisingly, the Omicron variant infection led to long-lasting instability in the gut microbiota and a notable depletion in Akkermansia muciniphila , even in the absence of severe lung pathology.…”
Section: Involvement Of Gut Microbial Community In Sars-cov-2 Pathoge...mentioning
confidence: 99%